2016
DOI: 10.1002/lary.26417
|View full text |Cite
|
Sign up to set email alerts
|

Altered pharyngeal structure and dynamics among patients with cervical kyphosis

Abstract: 3b. Laryngoscope, 127:1832-1837, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…PCR is defined as the ratio of the pharyngeal area measured in the lateral view at the point of maximum pharyngeal constriction to the area measured with a 1‐mL bolus held in the oral cavity and is a validated measure of pharyngeal contractility. An elevated PCR suggests diminished pharyngeal strength 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…PCR is defined as the ratio of the pharyngeal area measured in the lateral view at the point of maximum pharyngeal constriction to the area measured with a 1‐mL bolus held in the oral cavity and is a validated measure of pharyngeal contractility. An elevated PCR suggests diminished pharyngeal strength 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…[ 13 15 ] A retrospective analysis of data from video fluoroscopic swallow studies of 36 patients with cervical kyphosis confirmed the association between cervical kyphosis and altered pharyngeal structure and swallowing dysfunction. [ 16 ] The study revealed that patients with cervical kyphosis have a significantly dilated pharynx, elongated hypopharyngeal transit time, and worsened penetration–aspiration scores (the depth to which food passes in the airway). [ 16 ] Other retrospective studies[ 17 18 ] in patients treated with an external immobilization of the cervical spine (wearing a Halo-vest) showed significant association with the incidence of dysphagia, ranging from 32 to 66%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] The study revealed that patients with cervical kyphosis have a significantly dilated pharynx, elongated hypopharyngeal transit time, and worsened penetration–aspiration scores (the depth to which food passes in the airway). [ 16 ] Other retrospective studies[ 17 18 ] in patients treated with an external immobilization of the cervical spine (wearing a Halo-vest) showed significant association with the incidence of dysphagia, ranging from 32 to 66%. Miyagi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature and personal consultation with a specialist in otolaryngology indicates that there is no consensus regarding a protocol for performing VFSS in people with dysphagia (personal communication with Peter Belafsky MD, PhD, Medical Director of the Voice and Swallowing Center University of California, Davis). Unalike protocols are reported by different institutions in the United States currently publishing in this area of research (2325) although protocol consensus may be consistent loco-regionally or in different countries. The method for assessment of VFSS studies is also not standardized in people despite the fact that a comprehensive set of quantitative measures have been developed, reported and validated (26).…”
Section: Discussionmentioning
confidence: 99%